Synergetic Effects of PARP Inhibitor AZD2281 and Cisplatin in Oral Squamous Cell Carcinoma in Vitro and in Vivo - Yasukawa, Masaaki (Int J Mol Sci, 2016)
Cisplatin is a commonly used chemotherapeutic drug for treatment of oral carcinoma, and combinatorial effects are expected to exert greater therapeutic efficacy compared with monotherapy. Poly(ADP-ribosyl)ation is reported to be involved in a variety of cellular processes, such as DNA repair, cell death, telomere regulation, and genomic stability. Based on these properties, poly(ADP-ribose) polymerase (PARP) inhibitors are used for treatment of cancers, such as BRCA1/2 mutated breast and ovarian cancers, or certain solid cancers in combination with anti-cancer drugs. However, the effects on oral cancer have not been fully evaluated. In this study, we examined the effects of PARP inhibitor on the survival of human oral cancer cells in vitro and xenografted tumors derived from human oral cancer cells in vivo. In vitro effects were assessed by microculture tetrazolium and survival assays. The PARP inhibitor AZD2281 (olaparib) showed synergetic effects with cisplatin in a dose-dependent manner. Combinatorial treatment with cisplatin and AZD2281 significantly inhibited xenografted tumor growth compared with single treatment of cisplatin or AZD2281. Histopathological analysis revealed that cisplatin and AZD2281 increased TUNEL-positive cells and decreased Ki67- and CD31-positive cells. These results suggest that PARP inhibitors have the potential to improve therapeutic strategies for oral cancer.